Pre-feasibility assessment for identifying locations of new offshore wind projects in the Colombian Caribbean. - Bastidas-Salamanca , Martha; Bayona, Juan Gabriel (International Journal of Sustainable Energy Planning and Management, 2021)
The offshore wind energy sector is showing a growing interest because the increment of global energy demand and the commitment to reduce the CO2 emissions. The need to identify new wind offshore areas have motivated the development of methods where several quantitative and qualitative factors are considered. Then, this study reviewed these factors to establish a priority order to know when they could be analyzed within 3 main stages (pre-feasibility, feasibility and final decision). As a result, this research organized tha main factors in the 3 stages and performed a pre-feasibility analysis for assessing potential offshore areas considering technical-environmental features such as spatial classification, temporal variability (magnitude and direction) and geographical restrictions. The Colombian Caribbean coast was selected as study case, and 3 areas were identified according to their wind climate variability, in which 10 locations showed high potential for developing offshore wind projects. The north and central zone of the Colombian Caribbean coast were identified as the most suitable areas with mean annual wind-speed over 10 m/s with low magnitude and direction variability, two factors considered extremely important for the wind power generation.